Anestezjologia i intensywna terapia Comparison of sevoflurane and halothane anaesthesia on shunt and selected haemodynamic parameters during thoracosurgical procedures - Machała, Waldemar; Szebla, Renata; Perdeus, Jakub; Jabłoński, Sławomir; Gaszyński, Tomasz; Mamełka, Beata (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Background: One-lung ventilation (OLV) is a basic procedure used during lung surgery. OLV triggers increased shunt, which leads to a decrease of PaO2. Physiological mechanisms decreasing shunt volume such as hypoxic vascular vasoconstriction (HPV) may be disturbed, for example, by the position of the patient on the operating table, anaesthetics used, manipulation of operators and other factors. Aim: The authors studied the influence of two inhalatory anaesthetics, sevoflurane and halothane, on shunt and selected haemodynamic parameters (HR, MAP, MPAP, PCWP, CI, SVI, LVSWI, RWSVI, CPP, SVI and PVR). Material and methods: The study was carried out among 49 patients classified as physical status I or II on the ASA scale: the SEVO group (n=23) and HAL group (n=26), qualified for lung cancer operations (non-microcellular). Demographic parameters (weight, age, gender, BSI and BSA) as well as duration of anaesthesia and operation were comparable. The anaesthesia method – balanced: general (sevoflurane – SEVO, or halothane – HAL: concentration of 1 MAC) and regional (paravertebral/epidural continuous anaesthesia in thoracic segment (fentanyl)). Induction, muscle relaxant and analgesic agent doses were comparable in both groups. To monitor the haemodynamic parameters, a Swan-Ganz catheter was used. Results: Both anaesthetic agents had a similar impact on such haemodynamic parameters as HR, CI, MAP, SVI, LVSWI, SVR and PVR. Differences were observed in CVP, MPAP, RVSWI, PCWP and CPP. Conclusions: 1. Shunt in patients qualified for thoracosurgical procedures is much higher than the one considered physiological. 2. One-lung ventilation triggers an increase in shunt volume both in patients administered sevoflurane and those administered halothane. There are no significant statistical differences between anaesthetizing with sevoflurane and halothane. After anaesthesia, the shunt volume returns to what it was before anaesthesia only with patients who were administered sevoflurane. 3. The influence of the tested anaesthetics on haemodynamic parameters must be considered with respect to the influence on particular constituents of cardiac functions: • Sevoflurane and halothane have a similar influence on heart rate [HR] and cardiac index [CI]. • Halothane has a depressive influence on the left ventricle expressed mostly by an afterload decrease, which results in a decrease in coronary perfusion pressure [CPP]. The changes in CPP after sevoflurane administration do not have substantial statistical value. • Sevoflurane has a beneficial influence on the function of the right ventricle [↑RVSWI and ↓PVR].